Evaluation of Neutrophil Lymphocyte Ratio, Hyperbilirubinemia and Hyponatremia as a Predictive Marker of Complicated Appendicitis - Joshi, Prabesh; Poudel, Sudip; Nayak, Saroj; Ghimire, Surakshya; Sharma, Sarojini (Journal of Bharatpur Hospital, 2026)
Background Complicated appendicitis, including perforated and gangrenous forms, is associated with increased morbidity. This study evaluated the utility of NLR, hyperbilirubinemia, and hyponatremia as readily available preoperative biomarkers for predicting complicated appendicitis. Methods A prospective observational study was conducted between May 26, 2025, and December 25, 2025 among patients with clinically diagnosed acute appendicitis undergoing appendectomy. Preoperative laboratory parameters, including complete blood count, serum bilirubin, and serum sodium, were recorded, and NLR was calculated from absolute neutrophil and lymphocyte counts. Based on intraoperative findings, patients were classified as having uncomplicated or complicated appendicitis. Laboratory parameters were compared between groups, and statistical analyses were performed to assess their association with disease severity. Results A total of 91 patients were included, of whom 64 (70.3%) underwent appendectomy. The cohort comprised 41 males and 50 females, with a mean age of 30.75 ± 17.90 years and a mean BMI of 22.03 ± 5.79 kg/m². Among operated patients, 42 (65.6%) had non-complicated and 22 (34.4%) had complicated appendicitis. Mean NLR was higher in complicated cases (14.23 ± 17.5 vs. 7.7 ± 5.8), although the difference was not significant. Serum bilirubin was significantly elevated and serum sodium significantly lower in complicated appendicitis. ROC analysis identified hyponatremia as a strong predictor of complicated appendicitis. Conclusions Elevated NLR and serum bilirubin levels and reduced serum sodium levels are significantly associated with complicated appendicitis. These readily available laboratory markers, when used alongside clinical scoring systems such as the Alvarado score, can improve preoperative risk stratification and facilitate timely surgical intervention.